"Conocimiento Sobre Climaterio y Calidad de Vida en la Menopausia el Porvenir-Trujillo 2013 - Rondo Tolentino, María Ysabel (1543)
With the purpose of determining the influence of the level of knowledge about menopause in the quality of life in the menopause of women residents at the Sector Gran Chimú of district El Porvenir of the province of Trujillo during the period July - August 2013, a correlational cross-sectional descriptive study was conducted. He worked with a sample of 71 women of 40 to 60 years of age, which complied with the proposed inclusion criteria. Two instruments were applied: questionnaire for the level of knowledge about menopause (CNCC) and questionnaire specific of quality of life in the menopause (MENQOL). It was determined that: a) The level of knowledge about menopause is average by 56 percent, low at 26 percent and high by 18 percent; (b) The quality of life in menopause presented mild deterioration in the vasomotor area by 69 percent; moderate deterioration in the physical area by 45 percent; and severe deterioration in the sexual area by 22 percent; (c) There is influence significant knowledge about menopause in the quality of life in menopause in the areas of psycho-social, physical, and sexual (p < 0.05). There is no influence of knowledge about menopause in the quality of life in the vasomotor area. Key words: Knowledge upon climacteric, quality of life in menopause, women in menopause stage.